Students literal reading comprehension in term of main idea using manga comic - Andi Asri Jumiaty (Universitas Terbuka, 2023)
The aim of this research was to find out How Effective the use Manga comics in Students' Reading comprehension in literal tem of undersnading main idea. This research conducted by used Quantitative method with a Pre-Experimental design with one group of pre-test and post-test. This research population consisted of second semester students at English Education Department, Faculty of Teaching Training and Education of Universitas Muahhamdiyah Makassar, with the total 40 Students, selected by random sampling technique. The data from this study was gathered through the distribution of pre-test and post-test materials to be used as a comparison to determine how the improvement of students' reading comprehension in terms literal of understanding main idea before and after the use of manga comics as a teaching/learning media. The results showed that before treatment, students' average literal value was 51.00; after treatment, students' scores increased to 91.75, with a 79.90 increase in literal understanding. The improvement in students is classified as an increase in good criteria. Based on these findings, it is possible to conclude that there is a significant difference in students' reading comprehension before and after they use Manga Comics of teaching and learning process.